1986
DOI: 10.1111/j.1365-2621.1986.tb11181.x
|View full text |Cite
|
Sign up to set email alerts
|

High Fructose Corn Syrup Replacement for Sucrose in Shortened Cakes

Abstract: Cakes were prepared with high fructose corn syrup (HFCS) at 0, 50, and 75% replacement for sucrose to study the quality of cakes prepared with HFCS. Objective measurements showed that cakes prepared with HFCS were lower in volume, darker in crust and crumb color and no different in moisture content when compared with sucrose cakes. The taste panel found the sensory evaluation of the HFCS more moist and no different in crumb color. The 75% HFCS cakes were rated sweeter than the sucrose or the 50% HFCS. The sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Therefore, sucrose has more effect than monosaccharids on the formation of sugar-starch bridges (31). This result was confirmed by McCullough et al (1986) who used HFCS in replace of 0, 50 and 75% sucrose in shortened cake (32). Furthermore, Volpe and Meres (1976) implied to undesirable taste of sour flavor in white layer cakes in which HFCS was used in replace of 60% sucrose.…”
Section: Effect Of Hfcs On Bakery Products Propertiessupporting
confidence: 70%
“…Therefore, sucrose has more effect than monosaccharids on the formation of sugar-starch bridges (31). This result was confirmed by McCullough et al (1986) who used HFCS in replace of 0, 50 and 75% sucrose in shortened cake (32). Furthermore, Volpe and Meres (1976) implied to undesirable taste of sour flavor in white layer cakes in which HFCS was used in replace of 60% sucrose.…”
Section: Effect Of Hfcs On Bakery Products Propertiessupporting
confidence: 70%
“…While 40% replacement with syrup had got the lowest score in the overall acceptance (only 7.03). These results agree with work by McCoullough et al [27], who reported that the taste panel rated the all sucrose cake significantly more acceptable than the cakes prepared with high fructose corn syrup because of the compact, lower volume.…”
Section: Sensory Evaluation Of Cakessupporting
confidence: 91%
“…Muffins containing HFCS‐90 demonstrated intense crust browning (Table 3) when compared with the full‐fat variation. High‐fructose corn sweetener can contribute to a more intense browning through the Maillard reaction 12 . Additionally, the fat‐reduced muffin containing only maltodextrin produced a dark crust.…”
Section: Resultsmentioning
confidence: 99%